2016
DOI: 10.1111/phn.12299
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Survivorship Care among Latina Women with Breast Cancer in Los Angeles County

Abstract: This research lays a foundation for future work to develop interventions addressing Latina breast cancer survivors' unmet needs. Recommendations include enhancing peer and professional support services for patients, family, and caregivers. Further work is also needed to promote the implementation of survivorship care plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…This perceived responsibility, in addition to the stress of managing their diagnosis, treatment, and symptoms and side effects, led women to feel overwhelmed and unable to effectively manage their health. Similar findings have been observed in previous studies 31,32 that found that patients reporting confusion and anxiety regarding the continuity of care, and had unmet information needs with respect to SCPs are common. This study’s findings may be the result of the minimal involvement in the development and communication about their SCPs in the study sample.…”
Section: Discussionsupporting
confidence: 91%
“…This perceived responsibility, in addition to the stress of managing their diagnosis, treatment, and symptoms and side effects, led women to feel overwhelmed and unable to effectively manage their health. Similar findings have been observed in previous studies 31,32 that found that patients reporting confusion and anxiety regarding the continuity of care, and had unmet information needs with respect to SCPs are common. This study’s findings may be the result of the minimal involvement in the development and communication about their SCPs in the study sample.…”
Section: Discussionsupporting
confidence: 91%
“…The literature review on breast cancer survivorship and its determinants indicated significant unmet survivorship care needs among Latina breast cancer survivors including issues related to finance, symptom management, and survivorship care related information [4,25] and poor mental and physical health and low quality of life [26][27][28]. The determinants for the optimal use of SCP included knowledge about survivorship related issues [4,29,30], psychological distress (i.e., anxiety and fear concerning cancer recurrence) [26,27,31], and lack of confidence in patient-physician communication and management of chronic illness [30,32,33].…”
Section: Step One: Needs Assessmentmentioning
confidence: 99%
“…In comparison to non‐Latina White women, Latinas are more likely to (a) be diagnosed before age 50, (b) be diagnosed at an advanced stage, (c) have difficult to treat cancer types, and (d) have higher symptom burden 3,5–7 . They are also more likely to report unmet needs related to finances, continuity of care, information, and symptom management 3,8,9 . Thus, it is important to develop infrastructure, expand psychosocial supports, and understand the factors that facilitate women's access to these supports 3,9–11 .…”
Section: Introductionmentioning
confidence: 99%
“…3,[5][6][7] They are also more likely to report unmet needs related to finances, continuity of care, information, and symptom management. 3,8,9 Thus, it is important to develop infrastructure, expand psychosocial supports, and understand the factors that facilitate women's access to these supports. 3,[9][10][11] In particular, research is needed to examine ways to enhance access for Latina women who traditionally have been underserved-those who immigrated to the United States, whose primary language is Spanish, and who have limited access to health care.…”
mentioning
confidence: 99%
See 1 more Smart Citation